2003
DOI: 10.3136/fstr.9.237
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Low Salt Miso-Like Fermented Seasonings Using Soy-Oncom and Okara-Oncom (Fermented Soybeans and Okara with Neurospora intermedia) and Their Antioxidant Activity and Antimutagenicity

Abstract: To develop a new type of Miso, low salt miso-like fermented seasonings were prepared with soybean Oncom(SOncom) and Okara Oncom (O-Oncom): those were fermented soybeans and fermented Okara with Neurospora intermedia, respectively. Their antioxidant activity and antimutagenicity were analyzed and both Oncom had higher ␤-glucosidase activity than Koji (cooked rice molded with Aspergillus oryzae) with or without the presence of 4% salt and 2% ethanol. The strongest 1,1-diphenyl-2-picryl-hydrazyl radical scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These enzymes are essential for efficient in maceration and degradation of the essential ingredients (Oike et al, 1984). These results are in the line with (Matsuo and Takeuchi, 2003) who reported that soybean miso was a higher increase in soy bean miso than okara miso in chemical composition.…”
Section: Chemical Composition Of Misosupporting
confidence: 93%
“…These enzymes are essential for efficient in maceration and degradation of the essential ingredients (Oike et al, 1984). These results are in the line with (Matsuo and Takeuchi, 2003) who reported that soybean miso was a higher increase in soy bean miso than okara miso in chemical composition.…”
Section: Chemical Composition Of Misosupporting
confidence: 93%
“…The similarity between the texture of okara and fermented SB paste (i.e., miso) led to a series of studies, by Matsuo and Takeuchi, on the health benefits and palatability of an okara-miso-based condiment [164,165]. The okara-miso was prepared in several steps: okara-oncom and soy-oncom were prepared for inoculation with intermediate Neurospora.…”
Section: Production Of Food Fermented By Fungimentioning
confidence: 99%
“…Isoflavoneaglycons are bitterer than their glucosides (32). The taste of O-seasoning was slightly bitter (31). No significant difference was detected between the palatability of the taste of C-miso and S9O1-miso (Table 3).…”
Section: Antimutagenicitymentioning
confidence: 81%